Telkom 3010 Inside Story - Arwin Rasyid (PT Kompas Media Nusantara, 2016)
Armed with the trust placed in him by the Government, Arwin was determined to make Telkom a Fortune Global 500 company with a market value of USD 30 billion by 2010. Having served for less than half of his term, he and his team had successfully doubled the market capitalization of the state-owned telecommunications giant so that it accounted for more than 16 percent of the total value of the Indonesian stock market. Both market players and the company’s other stakeholders warmly welcomed the various strategic initiatives he introduced to boost the company’s value. ”Telkom3010: Inside Story Telkom Value Creation” recounts the winding and challenging journey of a CEO with a background in the financial services industry in managing the country’s leading infocom player. This book should be read by professionals and potential future business leaders.